Penelitian Efek Penggunaan Grid Tie Inverter pada Sistem Hibrid dengan Solar Panel dan Diesel - Suhaeri; Masri; Azhar; Saifuddin (Journal of Engineering and Science, 2023)
The distribution system of electrical power begins from generation and is transmitted to the load, namely consumers. In this distribution, it must be effective, efficient, and reliable. The amount of electrical power reaching the load is not the same as the amount of power generated due to voltage drop or power losses. This research aims to determine the magnitude of power losses in the medium-voltage distribution network located in Pasar Aceh. The research method employed is the analysis and simulation calculation method using ETAP 12.6 software. The study analyzes power losses due to load imbalance in the JTR distribution substation of Pasar Aceh. Based on the analysis results, the load imbalance in the Pasar Aceh substation has led to power losses. The power losses in the Pasar Aceh substation, specifically at the Side Transformer of Pasar Aceh, are 0.77% with a load imbalance of 16.33%. For the second transformer in the BNI 46 area, the power losses are 0.98% with a load imbalance of 30.33%, and for the transformer in the BLKG KOTTY area, the power losses are 1.17% with a load imbalance of 50.33%. Therefore, the larger the percentage of load imbalance in an electrical distribution network, the greater the resulting power losses.